Folklore and Literature: Canadian Contexts - Freake, Douglas; Henderson Carpenter, Carole (Ethnologies, 1999)
This article argues that the relation between folklore and literature in Canadian culture has significant characteristics that are closely related to the country’s formulations of its cultural identities. While Quebec writers have glorified their pre-Conquest past (or attacked sentimental folklorism), Ontario and other anglophone writers have tended to deny English folk culture while drawing on First Nations, Celtic and, more recently, “multicultural” folklore as sources for literature. Yet writers like Alice Munro are in fact among the best recorders of their group’s folkways, offering thick descriptions of ways of life that are disappearing as well as of contemporary folkways. In recent Canadian literature the binary opposition between literature and folklore has largely broken down, and in many texts imitations of the characteristics of oral discourse indicate writers’ validation of folklore over “literature.”